Meta Analysis: Learning Model Problem Based Learning (PBL) To Improve Mathematical Creative Thinking Skills - Kolili Kolili; Stevanus Budi Waluya; Bambang Eko Susilo (EduMa: Mathematics education learning and teaching, 2025)
Creative thinking skills are essential for all students. Each student must develop creative thinking skills to understand complex problems and generate diverse perspectives, ideas, and solutions. This study employed meta-analysis. The population comprised junior high school students. The samples used varied for each article reviewed. The total sample size was 148 students in the experimental class and 152 students in the control class. Hypothesis testing was conducted using a t-test.t. Calculations to test the hypothesis, obtained valuesamounting to 9.2176 whileof 1,649. Because for rejected, so it can be concluded that the average of the experimental class is more than the control class, this shows thatProblem Based Learning(PBL) as a learning model has a significant influence on students' mathematical creative thinking abilities. Based on research findings, the ModelProblem Based Learning(PBL) can be recommended as one of the learning approaches used in schools, especially to improve creative thinking skills.